Purification, crystallization and preliminary X‐ray crystallographic analysis of a rice Rac/Rop GTPase, OsRac1. Issue 1 (1st January 2014) - Kosami, Ken‐ichi; Ohki, Izuru; Hayashi, Kokoro; Tabata, Ryo; Usugi, Sayaka; Kawasaki, Tsutomu; Fujiwara, Toshimichi; Nakagawa, Atsushi; Shimamoto, Ko; Kojima, Chojiro
<x xml:space="preserve">Abstract</x> Small GTPases regulate a large variety of key cellular processes. Plant small Rac/Rop GTPases have recently received broad attention as it is becoming clear that these enzymes regulate various plant cellular processes. OsRac1, a rice Rac/Rop protein, is a key regulator of reactive oxygen species (ROS) production and induces immune responses. Although four structures of plant small GTPases have been reported, all of these were of the inactive form. Here, OsRac1 was purified and co‐crystallized with the GTP analogue 5′‐guanylyl imidodiphosphate (GMPPNP). The crystal belonged to space group P212121 and a complete data set was collected to 1.9 Å resolution.